Literasi Keuangan Syariah sebagai Instrumen Peningkatan Partisipasi Masyarakat dalam Perbankan Syariah: Analisis Yuridis terhadap Implementasi Prinsip-Prinsip Hukum Perbankan - Putri, Sherenika; Ekawahyuni, Nur Aini; Ervansyah, Muhammad Azriel; Kurniawan, Alia Herawati; Baidhowi (Jurnal Riksa Cendikia Nusantara, 2026)
This study aims to examine the role of Islamic financial literacy in increasing public participation in Islamic banking, from the perspective of Islamic banking law in Indonesia. The method used is a normative legal approach with a conceptual approach through literature review. The results of the study indicate that financial literacy in Islamic finance plays an important role not only as an educational tool but also as a normative instrument related to the principles of transparency, consumer protection, and balance in the legal relationship between banks and customers. Low literacy levels can lead to information imbalances and disputes, while increased literacy has been shown to foster public trust and participation. In addition, literacy serves as a preventative tool to reduce banking disputes. However, its implementation still faces challenges such as low public understanding and limited access to information. Therefore, more comprehensive and sustainable policy strengthening and education are needed.